Стан ценопопуляцій Cypripedium calceolus L. (Orchidaceae Juss.) у Буковинському Прикарпатті - Tokaryuk, A.I.; Chornej, I.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of research of the khorologycal, ecological, coenotical and population specialities of Cypripedium calceolus L. in the Bukovynske Prykarpattya are given.